2020
DOI: 10.1088/1361-6641/aba0cb
|View full text |Cite
|
Sign up to set email alerts
|

Polarization doping modulated heterojunction electron gas in AlGaN/GaN CAVETs

Abstract: A common AlGaN/GaN current-aperture vertical effect transistor (CAVET) with a SiO 2 current blocking layer on the GaN substrate is compared to two similar structures with the stepped and linearly graded AlGaN barrier layer, respectively. The approach resulted in high threshold voltages (V th ) of −2.6 V and −3.6 V, compared to V th = −4.4 V for the common device. And the breakdown voltage of two modified CAVETs was increased from 541 V to 711 V and 613 V, respectively. This reveals the great potential of polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…[ 257–259 ] For the cost and process‐simplifying consideration, several quasivertical GaN power diodes and transistors on the foreign substrates were developed, which consist of the vertical drift region and lateral spreading layers. [ 260–264 ] In particular, the current aperture vertical electron transistor (CAVET) [ 265–268 ] and trench CAVET [ 269–271 ] can operate the device by controlling the 2DEG channel, similarly to the lateral GaN HEMTs. Recently, the advanced vertical and quasi‐vertical GaN Schottky barrier diodes (SBDs), [ 253,272,273 ] junction barrier Schottky diodes, [ 274 ] fin MOSFETs, [ 275 ] trench MOSFETs, [ 276 ] superjunction diodes [ 277 ] and PN diodes [ 278–280 ] have successively raised the V BD from 600 to 4000 V with low R on .…”
Section: Discussionmentioning
confidence: 99%
“…[ 257–259 ] For the cost and process‐simplifying consideration, several quasivertical GaN power diodes and transistors on the foreign substrates were developed, which consist of the vertical drift region and lateral spreading layers. [ 260–264 ] In particular, the current aperture vertical electron transistor (CAVET) [ 265–268 ] and trench CAVET [ 269–271 ] can operate the device by controlling the 2DEG channel, similarly to the lateral GaN HEMTs. Recently, the advanced vertical and quasi‐vertical GaN Schottky barrier diodes (SBDs), [ 253,272,273 ] junction barrier Schottky diodes, [ 274 ] fin MOSFETs, [ 275 ] trench MOSFETs, [ 276 ] superjunction diodes [ 277 ] and PN diodes [ 278–280 ] have successively raised the V BD from 600 to 4000 V with low R on .…”
Section: Discussionmentioning
confidence: 99%
“…[25] Since then, several other CAVET demonstrations have been made. [14,26,27] The CAVET device design in GaN (to an extent) is analogous to the D-MOSFET, which has been explored in Si and SiC. [15] The CAVET utilizes a lateral AlGaN/GaN 2D electron gas (2-DEG) based highly conductive channel.…”
Section: Cavetmentioning
confidence: 99%
“…The regrowth and planarization processes may result in some leakage issues in the off state as discussed in the literature. [ 14,26–28 ] However, Nie et al have reported a high performing, normally‐off 1500 V, 2.2 mΩ cm 2 device, thus, demonstrating the potential of this device design. [ 14 ] Recently, Tanaka et al have demonstrated ion implantation based 1.2 kV vertical GaN planar MOSFET with low on‐resistance of 1.4 mΩ cm 2 .…”
Section: Vertical Gan Devices: Statusmentioning
confidence: 99%
“…Research on what methods are used to improve the conduction characteristics of vertical devices has become a hot spot in this field. The introduction of structures such as P-buried layer [13], superjunction (SJ) [14]- [17] and current barrier layer (CBL) of SiO 2 material [18] has promoted the improvement of vertical device performance and laid the foundation for the current demand for a wider range of applications. However, the existing technology to reduce the specific on-resistance (R onA ) of vertical devices is still relatively limited.…”
Section: Introductionmentioning
confidence: 99%